(untitled) (Journal of Parents and Teachers, 2025)
The article discusses the types of families that exist and the communication established within the family environment. It highlights various forms of pathological communication, each with its own background, such as contradictory, ambiguous, exclusionary, decentered, reciprocal dissociations, and labeling. Additionally, it addresses the psychological management of children and the different dynamics that may arise with various children.